Improving the effectiveness of H. pylori eradication therapy: focus on patient compliance and treatment safety - M. D. Ardatskaya; T. B. Topchiy; L. I. Butorova; E. V. Sayutina; E. M. Tuaeva; Yu. N. Loschinina; M. P. Egorycheva; N. N. Makarova; N. Yu. Anikina; G. F. Saidova; E. G. Melnikova; L. N. Proskuratova; et al. (Лечащий Врач, 2021)
The aim was to evaluate the effect of the combined butyrate and inulin supplement administered as an adjuvant to Helicobacter pylori eradication therapy (ET) on treatment outcome. 349 patients with chronic gastroduodenal diseases and infected H. pylori were еxamined. A comparative analysis of the effect of a combined butyrate and inulin supplement on improving the effectiveness of the optimized ET regimen, improving its tolerability and patients’ compliance. The success of eradication was controlled by a 13C urease breath test. Significantly higher eradication rates were observed in the ET + combined butyrate and inulin supplement group (91,3% versus 74,4%, р˂ 0,05), compared with the control group (ET only). A lower incidence of side effects (bloating, rumbling, diarrhea, bitterness in the mouth) by the end of the 14-day course of treatment was noted in the ET + combined butyrate and inulin supplement group (p˂ 0,01). Significantly higher patient adherence rates (87% versus 63%, p = 0.04) and a lower discontinuation rates of ET (χ2 = 8.22, p = 0.0041) were also noted in the ET + combined butyrate and inulin supplement group, compared with control group (ET only). The adjuvant administration of a combined supplement of butyric acid and inulin to a standard three-component ET regimen significantly increases the effectiveness of treatment and is associated with less self-reported side effects (diarrhea, bloating, bitterness in the mouth), lower side effects-related treatment discontinuation rates and higher treatment compliance.